Sensitivity analysis of material microstructure effects on predicted crack paths using finite element simulations - Jacob, Anaïs; Mehmanparast, Ali (World Scientific Publishing, 2016)
The effects of microstructure, grain and grain boundary (GB) properties on predicted damage paths and indicative crack propagation direction have been examined for a polycrystalline material using mesoscale finite element simulations. Numerical analyses were carried out on a compact tension specimen geometry containing granular mesh structures with random grain shapes and sizes of average diameter 100μμm. Nanoindentation tests were performed to investigate the dependency of mesoscale hardness measurements on the indentation location with respect to grain and GB regions. Finite element results have shown that under tensile loading conditions, the predicted damage paths are very sensitive to the granular mesh structure, GB properties and individual grain properties. Furthermore, finite element results have revealed that the cracking mode (i.e., transgranular/intergranular) and maximum crack deviation angle are strongly dependent on the material microstructures employed in simulations. Read More: http://www.worldscientific.com/doi/10.1142/S1756973716500037
Keywords: Damage path; Crack path; Mesoscale finite element modeling; Granular mesh structure; Microstructure; Polycrystalline material